Endoscopic application of clipping, over-the-scope clip (OTSC) and stenting for a fistula and anastomotic leakage of upper gastro-intestinal tract. Issue 3 (2019) - Makino, Hiroshi; Nomura, Satoshi; Maruyama, Hiroshi; Yokoyama, Tadashi; Hirakata, Atsushi; Kikuchi, Yuta; Yoshioka, Masafumi
No abstract available